Pemilihan Bagian Objektifitas Film Sejarah sebagai Media Pembelajaran - Ilyas, Yusran; zaharah, zaharah (Sosio-Didaktika: Social Science Education Journal, 2023)
This article explains how to select objective parts of historical films that will be used as learning media. That historical films not only visualize historical actors but also the atmosphere of a situation as a background for a historical event. Therefore, historical films are very susceptible to subjectivity. On the other hand, historical sources do not perfectly describe past events, but only describe events that are considered important. This article emphasizes that history teachers have the skills to select parts of films that measure their objectivity. This article uses historical research methods in the form of source collection, source criticism, interpretation, and writing. This article's contribution is not only limited to exploring the educational values of a historical film, but also to providing tools for history teachers in selecting fragments of events in historical films that have proven objectivity.